Induction, regulation and roles of neural adhesion molecule L1CAM in cellular senescence - Mrazkova, Blanka (Aging (Albany NY), 2018)
Aging involves tissue accumulation of senescent cells (SC) whose elimination through senolytic approaches may evoke organismal rejuvenation. SC also contribute to aging-associated pathologies including cancer, hence it is imperative to better identify and target SC. Here, we aimed to identify new cell-surface proteins differentially expressed on human SC. Besides previously reported proteins enriched on SC, we identified 78 proteins enriched and 73 proteins underrepresented in replicatively senescent BJ fibroblasts, including L1CAM, whose expression is normally restricted to the neural system and kidneys. L1CAM was: 1) induced in premature forms of cellular senescence triggered chemically and by gamma-radiation, but not in Ras-induced senescence; 2) induced upon inhibition of cyclin-dependent kinases by p16(INK4a); 3) induced by TGFbeta and suppressed by RAS/MAPK(Erk) signaling (the latter explaining the lack of L1CAM induction in RAS-induced senescence); and 4) induced upon downregulation of growth-associated gene ANT2, growth in low-glucose medium or inhibition of the mevalonate pathway. These data indicate that L1CAM is controlled by a number of cell growth- and metabolism-related pathways during SC development. Functionally, SC with enhanced surface L1CAM showed increased adhesion to extracellular matrix and migrated faster. Our results provide mechanistic insights into senescence of human cells, with implications for future senolytic strategies.